Antiquarianism, Patriotism and Empire: Transfers of the Cartography of The Travels of Anacharsis the Younger in Greece (1788-1811) - Tolias, George (The Historical Review/La Revue Historique, 2006)
The aim of this paper is to present an instance of cultural transfer within the field of late Enlightenment antiquarian cartography of Greece, examining a series of maps printed in French and Greek, in Paris and Vienna, between 1788 and 1811 and related to Abbé Barthélemy’s Travels of Anacharsis the Younger in Greece. The case study analyses the alterations of the content of the work and the changes of its symbolic functions, alterations due first to the transferral of medium (from a textual description to a cartographic representation) and next, to the successive transfers of the work in diverse cultural environments. The transfer process makes it possible to investigate some aspects of the interplay of classical studies, antiquarian erudition and politics as a form of interaction between the French and the Greek intelligentsia of the period.